2019
DOI: 10.1109/access.2019.2940487
|View full text |Cite
|
Sign up to set email alerts
|

Movements and Balance Control of a Wheel-Leg Robot Based on Uncertainty and Disturbance Estimation Method

Abstract: In order to control the posture, balance and movements of a wheel-leg robot(WLR) precisely, some problems have to be solved. The major problems involve the strongly coupling of movement states, the composite uncertainty with modeling errors, the time-varying internal and the external disturbances. In this paper, a force controller based on the uncertainty and disturbance estimation(UDE) method is designed. The feedforward compensation based on dynamic model allows for compliant and more precise motion control.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…In this case, it is enough to choose strictly proper stable first-order low pass filter G f (s) = [1/(Ts + 1)] with a time constant T [5]. Replace d with u d in (6), there is (8) Substituting ( 8) to (3), there is…”
Section: Control Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, it is enough to choose strictly proper stable first-order low pass filter G f (s) = [1/(Ts + 1)] with a time constant T [5]. Replace d with u d in (6), there is (8) Substituting ( 8) to (3), there is…”
Section: Control Algorithmmentioning
confidence: 99%
“…The proposed method prevents the singularity problem of the controller, which might be influenced by the inverse operation. Design of robustness of movements balance controller in wheelleg robot [8], trajectory tracking control of underwater vehicle-manipulator systems [9], interaction control with an uncertain robot and its unknown environment [10], and bounded UDE-based control for a quadrotor [11] are some more examples to cite.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments showed that this method could achieve good trajectory tracking and interference suppression. Xin et al [ 12 ] established a motion balance controller for a WBR based on the inverse dynamics and uncertainty and disturbance estimation (UDE) method, and verified the robustness of the method by simulations. Wang et al [ 13 ] proposed an interconnection and damping assignment-passivity-based control (IDA-PBC) method, which can enable the WBR to obtain a wide range of stability.…”
Section: Introductionmentioning
confidence: 99%
“…As the highly coupled nonlinear characteristics, the actuator fault causes obvious effects on the system dynamics; therefore, they can be easily detected through monitoring abnormal system performances. Following the literature of actuator fault detection and isolation, and estimation, such fault can be considered as matched or mismatched disturbances and observed by using observers such as extended state observers (ESO) [15], [18], [19], disturbance observers (DO) [12], [20]- [22], uncertainty and disturbance estimator (UDE) [23], [24], time-delayed estimation (TDE) [25]- [27], super-twisting algorithm [28], Kalman estimators [29], unknown input observer [30], [31], etc. Then, Fault-tolerant control (FTC) that combines these observers compensation with advanced control algorithms such as active disturbance rejection control (ADRC) [32], [33], adaptive algorithms [34]- [36], or high robust gains can be employed to address the influence of the actuator fault.…”
Section: Introductionmentioning
confidence: 99%